# Nth Term of a Geometric Sequence

What is the nth term of a geometric sequence? Let A(n) be the value of the nth term of the geometric sequence.

Let n be the term number in the sequence.

Let A(1) = a be the first term of the sequence.

Then, the function rule for the nth term is A(n) = a × rn-1

Notice that when n = 1,

A(1) = a × r1-1

A(1) = a × r0

A(1) = a × 1 = a

## How to write the function rule for the nth term of a geometric sequence

Consider the sequence 2, 10, 50, 250, 1250, ...

A(1) = 2

A(2) = 2 × 5 = 2 × 51

A(3) = 2 × 5 × 5 = 2 × 52

A(4) = 2 × 5 × 5 × 5 = 2 × 53
.
.
.

A(n) = 2 × 5 × 5 × 5 × 5 ... × 5 = 2 × 5n-1

Notice that each exponent is one less than its term number.

The function rule for 2, 10, 50, 250, 1250, ... is A(n) = 2 × 5n-1

## Using the function rule of a geometric sequence to quickly solve a real life problem

A woman invests some money in the stock market. Her initial investment is 4000 dollars. Suppose the amount at the beginning of the second year is 75% of the initial investment. Then, each amount is 75% of the previous amount. How much money does she have after 4 years?

Solution

A(n) = 4000 × 0.75n-1

Notice that when n = 1,

A(1) = 4000 × 0.751-1 = 4000 × 0.75=  4000 × 1 = 4000

Therefore, A(2) is money after 1 year, A(3) is money after 2 years, and A(5) is money after 4 years.

A(5) = 4000 × 0.755-1

A(5) = 4000 × 0.754

A(5) = 4000 × 0.31640625

A(5) = 1265.625

After 4 years, she has 1265.625 dollars.

Enjoy this page? Please pay it forward. Here's how...

Would you prefer to share this page with others by linking to it?

1. Click on the HTML link code below.
2. Copy and paste it, adding a note of your own, into your blog, a Web page, forums, a blog comment, your Facebook account, or anywhere that someone would find this page valuable.
Share this page: